STUDY ON OCCURRENCE AND MANAGEMENT OF ALVEOLAR OSTEITIS - V. P, Pathmashri.; Kumar, Dinesh; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
A dry socket, also referred to as alveolar osteitis, is a postoperative complication that interferes with the healing process that takes place after a tooth extraction. “Dry socket” was first described by Crawford in 1896. It occurs when the tooth socket loses the blood clot that forms after the tooth is extracted and the bone inside the socket is exposed. It occurs in 0.5-5% of routine dental extractions and 25-30% in the extraction of impacted mandibular third molars. Clinically, an empty socket that lacks a blood clot and exposed bone is seen. The socket may be filled with a food debris and saliva mixture. Pain starts 24-72 hours after extraction. It varies in frequency and intensity and radiates to the ear and neck. It is not characterized by redness, swelling, fever, or pus formation, but edema of the surrounding gingiva and regional lymphadenitis are present. Histological features of dry socket are remnants of the blood clot and a massive inflammatory response characterized by neutrophils and lymphocytes, which may extend into the surrounding alveolus.